"Cluster Bomb" Based Bismuth Nano‐in‐Micro Spheres Formed Dry Powder Inhalation for Thermo‐Radio Sensitization Effects of Lung Metastatic Breast Cancer. Issue 11 (16th January 2023) - Wang, Qiyue; Liu, Ji; Chen, Daquan; Miao, Si; Wen, Jing; Liu, Chang; Xue, Shushu; Liu, Yang; Zhang, Qingjie; Shen, Yan
Abstract: Lung metastatic breast cancer (LMBC) is mainly diagnosed through CT imaging and radiotherapy could be the most common method in the clinic to inhibit tumor proliferation. While the sensitivity of radiotherapy is always limited due to the hypoxic tumor microenvironment and high doses of irradiation easily induce systemic cytotoxicity. Metal‐based materials applied as radiosensitizers have been widely investigated to improve efficiency and reduce the doses of irradiation. Herein, it is aimed to overcome these problems by designing biodegradable lipid‐camouflaged bismuth‐based nanoflowers (DP‐BNFs) as both a photo‐thermo‐radiosensitizer to develop a novel photothermal therapy (PTT) and radiotherapy combination strategy for LMBC treatment. To achieve effective lung deposition, "Cluster Bomb" structure‐based DP‐BNFs nano‐in‐micro dry powder inhalation (DP‐BNF@Lat‐MPs) are formulated through spray‐dried technology. The DP‐BNFs "cluster" in the microsphere to improve their tumor‐targeted lung deposition with a high fine particle fraction followed by burst releasing of DP‐BNFs for targeting delivery and LMBC therapy. The DP‐BNF@Lat‐MPs exhibit excellent photothermal conversion efficiency, radiotherapy enhancement, and CT imaging ability in vitro, which synergistically inhibit cell proliferation and metastasis. In vitro and in vivo data prove that combining PTT and radiotherapy with DP‐BNF@Lat‐MPs as a thermo‐radio dual‐sensitizer significantly enhances LMBC tumor metastasis inhibition with good biocompatibility and low toxicity. Abstract : The DP‐BNFs "cluster" in the lactose microsphere to formulate DP‐BNFs nano‐in‐micro dry powder inhalation (DP‐BNF@Lat‐MPs) with high tumor‐targeted lung deposition. The DP‐BNF@Lat‐MPs exhibit excellent photothermal conversion efficiency, radiotherapy enhancement, and CT imaging ability in vitro, which synergistically improve the synergistic therapeutic efficiency of PTT and radiotherapy in BCLM treatment.